Efektivitas Penyaluran Dana Talangan Haji untuk Proses Percepatan Keberangkatan Haji - Ana Nurwakhidah; Ardhelia Setyo Risma; Mas Nur Chayati (Lembaga Pengembangan Kinerja Dosen, 2024)
IB Hijrah advance fund is one of the products offered by Bank Muamalat to customers, in this product there is an offer of advance funds specifically for customers who want to perform the Hajj pilgrimage but are still constrained by costs. Not only the existing product offerings, the service system is also an important factor that can affect the success of a company in selling its products. In addition to conducting large-scale promotions, it must also be supported by good service so that the desired results are maximized and effective. Effectiveness is a measure that states how far the target has been achieved and measures the level of success of the predetermined target.